2019
DOI: 10.1021/acsami.9b00034
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Omnidirectional Broadband Light-Management Coating Using the Hierarchical Ordered–Disordered Nanostructures with Ultra-Mechanochemical Resistance

Abstract: High-efficient light-management nanostructures are critical to various optical applications. However, in practical implementation, these structures have been limited by the need to resist mechanical abrasion, erosion, chemical exposure, ultraviolet radiation, and performance deterioration by dust accumulation. To address these critical technological gaps, we herein report a conceptually different approach, employing a hierarchical nanostructure embedded with multilayer LightScribe-etched graphene, capable of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…For outdoor light-management films in practical application, dust accumulation is always the main challenge. 25 To broaden the applicability and durability of light-management films in diverse fields, integrating the superhydrophobic surface with a self-cleaning function into the films is a promising strategy. 26 Recently, many studies have been reported to enhance the hydrophobic performance of films.…”
Section: Introductionmentioning
confidence: 99%
“…For outdoor light-management films in practical application, dust accumulation is always the main challenge. 25 To broaden the applicability and durability of light-management films in diverse fields, integrating the superhydrophobic surface with a self-cleaning function into the films is a promising strategy. 26 Recently, many studies have been reported to enhance the hydrophobic performance of films.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Finally, 4) Solar cells are equipped with a hazy layer solely to propagate sunlight ray distance via light scattering, which as a result, significantly boost the photoelectric conversion efficiency. [5][6][7][8][9] Flexible electronic substrates in any optoelectronic devices are mainly made of glass or plastic. Optical substrates market has been greatly influenced by plastics due to the low-cost and light weight characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of optical haze is described as the percentage of transmitted light through a substrate that diffusely scatters. This advantageous scattering of sunlight increases the absorption path of light, enhancing solar cell conversion efficiency [ 10 , 11 ]. The market for flexible thin-film solar cells has been influenced by plastic substrates, due to their low costs and light weight.…”
Section: Introductionmentioning
confidence: 99%